2016
DOI: 10.1038/srep33784
|View full text |Cite|
|
Sign up to set email alerts
|

Efficient delivery of C/EBP beta gene into human mesenchymal stem cells via polyethylenimine-coated gold nanoparticles enhances adipogenic differentiation

Abstract: The controlled differentiation of stem cells via the delivery of specific genes encoding appropriate differentiation factors may provide useful models for regenerative medicine and aid in developing therapies for human patients. However, the majority of non-viral vectors are not efficient enough to manipulate difficult-to-transfect adult human stem cells in vitro. Herein, we report the first use of 25 kDa branched polyethylenimine-entrapped gold nanoparticles (AuPEINPs) and covalently bound polyethylenimine-go… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 90 publications
(107 reference statements)
1
18
0
Order By: Relevance
“…Chemical non-viral methods employ liposomes, dendrimers, inorganic nanoparticles, magnetic nanoparticles (MNPs) or polymers as transfection agents. High transfection efficiency was reported using poly (ethylenimine) (PEI) in combination with gold or silica nanoparticles[ 54 , 55 ].…”
Section: Methods To Enhance Stem Cell Homingmentioning
confidence: 99%
“…Chemical non-viral methods employ liposomes, dendrimers, inorganic nanoparticles, magnetic nanoparticles (MNPs) or polymers as transfection agents. High transfection efficiency was reported using poly (ethylenimine) (PEI) in combination with gold or silica nanoparticles[ 54 , 55 ].…”
Section: Methods To Enhance Stem Cell Homingmentioning
confidence: 99%
“…Inorganic-gold nanoparticles (Olton et al, 2007;Arvizo et al, 2010;Ding et al, 2014;Wegman et al, 2014;Das et al, 2016;Yang et al, 2018) High biocompatibility. Tunable features (e.g., size and surface coatings).…”
Section: Advantages Limitations Applicationsmentioning
confidence: 99%
“…However, the application of nonviral systems in gene therapy has been limited due to their low transfection efficiency and transient expression of the transgene [ 92 ]. Liposomes and polymers are among traditional nonviral delivery systems shown that transiently transfect MSCs [ 90 , 93 95 ]. Minicircles are small DNA-based vectors lacking prokaryotic backbone sequences that are typically present in conventional plasmid vectors.…”
Section: Mesenchymal Stromal/stem Cells (Mscs)mentioning
confidence: 99%